A Fully Integrated Flexible Heterogeneous Temperature and Humidity Sensor‐Based Occupancy Detection Device for Smart Office Applications. Issue 12 (14th November 2019) - Naqi, Muhammad; Lee, Sungho; Kwon, Hyuk‐Jun; Lee, Min Goo; Kim, Minjung; Kim, Tae Whan; Shin, Hyun Kyu; Kang, Sunju; Gandla, Srinivas; Lee, Han‐Seung; Ahn, Yonghan; Lee, Sanghyo; et al.
Abstract: Heating, ventilation, and air conditioning systems in building operations have extensively gained significant interest in recent years for providing a comfortable environment and energy savings by utilizing the occupancy information of buildings. Herein, a flexible heterogeneous temperature and humidity sensor‐based occupancy detection device with an integrated wireless communication system is introduced. The multichannel (three‐channel) Pt‐based temperature and single‐channel humidity sensors afford excellent electrical conductivity, exceptional linearity, and high mechanical flexibility. The presented occupancy detection device design contains a multichannel temperature sensor, an interdigitated humidity sensor, a customized signal processing integrated circuit, a flexible battery, and a wireless communication system, which can be used to perform occupancy trials in offices. The proposed occupancy detection device is mounted on an office chair to analyze the environmental changes according to the user's activities and to address the challenge of long‐term continuous monitoring of temperature and humidity for managing the energy consumption in the building operations. The presented occupancy detection device provides a new platform for introducing a flexible device system to collect the actual occupancy information and is a new step toward "smart office" applications. Abstract : A flexible heterogeneous temperature and humidity sensor‐based occupancy detection device is proposed for real‐time monitoring of heating, ventilation, and air conditioning conditions in building systems. The proposed occupancy detection device is embedded on chair for continuous monitoring of temperature and humidity fluctuations in office space to enable thermal comfort for users as well as managing the energy consumption of building systems.